2015
DOI: 10.1111/cei.12723
|View full text |Cite
|
Sign up to set email alerts
|

DC-SIGN expression on podocytes and its role in inflammatory immune response of lupus nephritis

Abstract: SummaryPodocytes, the main target of immune complex, participate actively in the development of glomerular injury as immune cells. Dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) is an innate immune molecular that has an immune recognition function, and is involved in mediation of cell adhesion and immunoregulation. Here we explored the expression of DC-SIGN on podocytes and its role in immune and inflammatory responses in lupus nephritis (LN). Expression of DC-SIGN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Several genes decreased in aged female mice compared to young female mice, including those involved in xenobiotic metabolism (Inmt, Hpd, Ces1e) and Cluster of Differentiation 209 (Cd209a) (aka. Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin, DC-SIGN) ( Figure 2B ), which co-expresses with nephrin in podocytes [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several genes decreased in aged female mice compared to young female mice, including those involved in xenobiotic metabolism (Inmt, Hpd, Ces1e) and Cluster of Differentiation 209 (Cd209a) (aka. Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin, DC-SIGN) ( Figure 2B ), which co-expresses with nephrin in podocytes [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study evaluated the level of CD209 in psoriasis vulgaris lesions, and reported that CD209 was higher in psoriasis lesions compared with normal tissues [ 16 ]. A recent study showed the expression of CD209 on podocytes and its possible role in immune and inflammatory responses in lupus nephritis [ 42 ]. In this study, CD209 circulating granulocytes correlated with systemic scores, ESR, and levels of CRP, ferritin, LDH, IL-23, and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…10 DC-SIGN is co-expressed with nephrin on podocytes in the renal tissues of patients with lupus nephritis. 11 There is a significant correlation between DC-SIGN expression on the tubulointerstitium and the severity of tubulointerstitial lesions. 12 Thus it appears that the expression of DC-SIGN on non-immune cells may modulate the outcomes of the disease.…”
Section: Introductionmentioning
confidence: 99%